International Centre for Settlement of Investment Disputes as an effective me chanism of dispute resolution between an investor and a state - Babkina, Elena V.; Khomenko, Maria V. (Journal of the Belarusian State University. International Relations, 2018)
In this article, the authors discuss an effective mechanism of investment dispute resolution at the International Centre for Settlement of Investment Disputes (ICSID). In particular, the authors analyze its structure and jurisdiction rationemateriae and ratione personae, focusing on the problems of applying an umbrella clause. Specifically, ICSID jurisdiction rationemateriae includes disputes of a legal nature that arise directly out of an investment. The authors discuss deviation from a classic interpretation of the term “investment”, which traditionally included such components ascontribution, certain duration of the performance of the contract, and assumption of risks arising from the investment agreement and which was later supplemented with factors like contribution to the host state’s economy (Salini test) and bone fide performance. ICSID jurisdiction ratione personae, in turn, includes individual entrepreneurs and juridical persons, regardless of their status as a business entity. Nationality of a juridical person is determined in accordance with the principles of international private law (e. g., by the place of its incorporation, principal business operations, or central administrative offices). However, a place of management and control of an investor is often considered as an important criterion in determining its nationality as well. It is generally determined based on all facts and circumstances by analyzing the number of shares owned by the foreign investor, its decision-making power, and the ability to participate in the company’s management. Lastly, in this article, the authors also discuss the various ways of expressing consent to ICSID jurisdiction by the parties.